Robotic Exoskeletons: A Perspective for the Rehabilitation of Arm Coordination in Stroke Patients - Jarrassé, Nathanaël; Proietti, Tommaso; Crocher, Vincent; Robertson, Johanna; Sahbani, Anis; Morel, Guillaume; Roby-Brami, Agnès (Frontiers in Human Neuroscience, 2014)
Upper-limb impairment after stroke is caused by weakness, loss of individual joint control, spasticity and abnormal synergies. Upper limb movement frequently involves abnormal, stereotyped and fixed synergies, likely related to the increased use of subcortical networks following the stroke. The flexible coordination of the shoulder and elbow joints is also disrupted. New methods for motor learning, based on the stimulation of activity-dependent neural plasticity have been developed. These include robots that can adaptively assist active movements and generate many movement repetitions. However, most of these robots only control the movement of the hand in space. The aim of the present text is to analyse the potential of robotic exoskeletons to specifically rehabilitate joint motion and particularly inter-joint coordination. Firstly, a review of studies on upper-limb coordination in stroke patients is presented and the potential for recovery of coordination is examined. Secondly, issues relating to the mechanical design of exoskeletons and the transmission of constraints between the robotic and human limbs are discussed. The third section considers the development of different methods to control exoskeletons: existing rehabilitation devices and approaches to the control and rehabilitation of joint coordinations are then reviewed, along with preliminary clinical results available. Finally, perspectives and future strategies for the design of control mechanisms for rehabilitation exoskeletons are discussed.